2013
DOI: 10.5194/acp-13-819-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gobi desert dust on aerosol chemistry of Xi'an, inland China during spring 2009: differences in composition and size distribution between the urban ground surface and the mountain atmosphere

Abstract: Abstract. Composition and size distribution of atmospheric aerosols from Xi'an city (∼ 400 m, altitude) in inland China during the spring of 2009 including a massive dust event on 24 April were measured and compared with a parallel measurement at the summit (2060 m, altitude) of Mt. Hua, an alpine site nearby Xi'an. EC (elemental carbon), OC (organic carbon) and major ions in the city were 2-22 times higher than those on the mountaintop during the whole sampling period. Compared to that in the non-dust period … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 84 publications
6
54
0
Order By: Relevance
“…Such a correlation was also reported by other researchers Yu et al, 2005), suggesting the co-occurrence and internally mixing state of both compounds in the atmosphere. In addition, the previous field measurements also revealed that WSOM in China is not only enriched in carboxylic acids (including oxalic acid) but also in other organic species, including carbonyls, amines, and water-soluble nitrogen-containing organic compounds (G. Wang et al, 2010;Wang et al, 2013;Zheng et al, 2015;Yao et al, 2016;F. Liu et al, 2017).…”
Section: Field Measurements Of Wsom In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Such a correlation was also reported by other researchers Yu et al, 2005), suggesting the co-occurrence and internally mixing state of both compounds in the atmosphere. In addition, the previous field measurements also revealed that WSOM in China is not only enriched in carboxylic acids (including oxalic acid) but also in other organic species, including carbonyls, amines, and water-soluble nitrogen-containing organic compounds (G. Wang et al, 2010;Wang et al, 2013;Zheng et al, 2015;Yao et al, 2016;F. Liu et al, 2017).…”
Section: Field Measurements Of Wsom In Chinamentioning
confidence: 99%
“…Such an assumption is clearly invalid, as aerosols typically contain a large portion of WSOM in China (Fig. 3), including organic nitrogen species (G. Wang et al, 2010;Wang et al, 2013) and acids (G. Wang et al, 2009Wang et al, , 2010Wang et al, 2006). Also, organic acids engage in particle-phase reactions with the basic species (i.e., NH 3 and amines), significantly enhancing the particle hygroscopicity and reducing the acidity (GomezHernandez et al, 2016).…”
Section: Field Measurements Of Wsom In Chinamentioning
confidence: 99%
“…Figure 8 shows the vertical profiles of major organic species among the identified organics. It is noticeable that, with increasing altitude, concentrations of most organic species (e.g., levoglucosan, mannitol, phthalic acid, MBTCA, and pinic acid) decrease in both seasons, owing to the atmospheric dilution during upward transport from the ground surface (Simoneit et al, 1991;Gao et al, 2003;Feng et al, 2006;Fu et al, 2010;Wang et al, 2013). During the ACEAsia campaign, a large organic carbon aerosol source was observed in the free troposphere over the downwind regions of China (Heald et al, 2005), which is proposed to be mainly from isoprene-derived SOA (Henze and Seinfeld, 2006).…”
Section: Organic Nitrogen Speciesmentioning
confidence: 99%
“…In November we obtained relatively high OC / EC ratio. This may be caused by long-range atmospheric transport of biomass burning plumes from Southeast Asia because biomass burning is very common in the region in autumn (Wang et al, 2013b) and the air masses mostly came from Southeast Asia including Philippines (Fig. 2d).…”
Section: Seasonal Variations Of Oc / Ec and Wsoc / Oc Ratiosmentioning
confidence: 99%